2020
DOI: 10.1017/s0952675720000305
|View full text |Cite
|
Sign up to set email alerts
|

Weight and final vowels in the English stress system

Abstract: This paper presents both dictionary evidence and experimental evidence that the quality of a word's final vowel plays a role in assigning main stress in English. Specifically, a final [i] pushes main stress leftwards – three-syllable words ending with [i] have a strong tendency to take antepenultimate stress. This pattern is compared with the Latin Stress Rule for English, according to which words with heavy penultimate syllables should have penultimate stress. Both pressures are shown to be productive in expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Moreover, this finding is compatible with the assumption that the position of word stress can be determined by means of analogy (Guion et al 2003;Arciuli et al 2010;Burani et al 2014;Moore-Cantwell 2020).…”
Section: Naïve Vs Abstract Cuessupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, this finding is compatible with the assumption that the position of word stress can be determined by means of analogy (Guion et al 2003;Arciuli et al 2010;Burani et al 2014;Moore-Cantwell 2020).…”
Section: Naïve Vs Abstract Cuessupporting
confidence: 87%
“…In this way, the algorithm is able to represent stress assignment on the basis of phonological/orthographic neighbors, as has been demonstrated in previous studies (e.g. Guion et al 2003;Arciuli et al 2010;Burani et al 2014;Moore-Cantwell 2020).…”
Section: Modelling Approachmentioning
confidence: 75%
See 1 more Smart Citation
“…With this first test, I confirm this tendency while controlling for stress level and position in the word by considering only stressed initials of disyllables. The division between light and heavy syllables is nuanced in English (Moore-Cantwell 2021), but for present purposes, I follow Olejarczuk & Kapatsinski (2018: 385) in treating syllables ending with monophthongs except /i, u/ as light and those ending with /i, u/, codas, diphthongs and syllabic consonants (including the rhotic) as heavy. In DALI 2, heavy syllables as initials of disyllables are mapped onto quarter (i.e.…”
Section: Beyond Binary Weightmentioning
confidence: 99%
“…It is found that lexical parameters and audibility have influence on word speech recognition in monosyllabic speech test [2]. The quality of final vowels of words plays an important role in English major stress [3]. Acoustic cues of word stress promote offline and online language processing to a certain extent [4], because speakers are sensitive to auditory feedback in stressed and unstressed syllables [5].…”
Section: Introductionmentioning
confidence: 99%